2021
DOI: 10.1038/s41598-021-83826-5
|View full text |Cite
|
Sign up to set email alerts
|

High coercivity SmCo5 synthesized with assistance of colloidal SiO2

Abstract: SmCo5 is one of the most promising candidates for achieving a hard magnet with a high coercivity. Usually, composition, morphology, and size determine the coercivity of a magnet, however, it is challenging to synthesize phase pure SmCo5 with optimal size and high coercivity. In this paper, we report on the successful synthesis of phase pure SmCo5 with spherical/prolate spheroids shape. Size control is obtained by utilizing colloidal SiO2 as a template preventing aggregation and growth of the precursor. The amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…SmCo 5 was chosen as a filler due to the great attention paid to it in modern science and practice [ 56 , 57 ], namely due to its high coercive force, as well as resistance to corrosion and oxidation, which allows the use of composites based on it in humid and aggressive environments. It was found that SmCo 5 /HEMA-gr-PVP composites possessed magnetic properties after band magnetization using profile inductors.…”
Section: Resultsmentioning
confidence: 99%
“…SmCo 5 was chosen as a filler due to the great attention paid to it in modern science and practice [ 56 , 57 ], namely due to its high coercive force, as well as resistance to corrosion and oxidation, which allows the use of composites based on it in humid and aggressive environments. It was found that SmCo 5 /HEMA-gr-PVP composites possessed magnetic properties after band magnetization using profile inductors.…”
Section: Resultsmentioning
confidence: 99%
“…Particle size dependency of coercivity of SmCo 5 powder (Dong Y. et al, 2019;Li C. et al, 2018;Ma Z.-H. et al, 2017;Ma Z. et al, 2019a;Ma Z. et al, 2019b;Ma Z. et al, 2015;Shen B. et al, 2019;Tang H. et al, 2020a;Tang H. et al, 2021;Tang H. et al, 2020b;Wu Q. et al, 2020a;Zhang H. et al, 2011b). Tang (2020b) Ma ( 2015) Ma ( 2017) Tang ( 2021) Shen ( 2019) Dong ( 2019) Ma (2019a) Li ( 2018) Wu ( 2020) Ma (2019b) Zhang ( 2011) Tang (2020a) are free of the particle surface contamination which is a drawback of the chemical synthesis processes described in Section 2.1.2.…”
Section: Figmentioning
confidence: 99%